Algorithm for identifying chemotherapy/biological regimens for metastatic colon cancer in SEER-Medicare - Bikov, Kaloyan A; Mullins, C Daniel; Seal, Brian; Onukwugha, Eberechukwu; Hanna, Nader (Medical care, 2015)
Metastatic colon cancer (mCC) patients often receive multiple lines of chemotherapy/biological treatment (TX), yet subsequent TX lines have not been sufficiently examined using SEER-Medicare data. We developed an algorithm that identifies the number and type of TX lines received by mCC patients. The algorithm rules for detecting TX lines were developed a priori and applied to SEER-Medicare data for 7951 elderly mCC patients, diagnosed in 2003-2007 and followed through 2009. Statistical analysis estimated the relationship between the number of treatments received and patient characteristics. Sensitivity analyses examined how results changed when different algorithm rules were used. Only 41% (3266) of mCC patients received any chemotherapy/biologics treatment; 1440 (18% of all, 44% of treated) and 274 (3% of all, 8% of treated) received second-line and third-line treatment, respectively. Initial and subsequent treatment regimens varied widely. Results were robust to alterations in the algorithm. The number of drugs used to treat cancer patients has increased during the past decade. Patients may have several TX lines with complex regimens. More guidance is needed with regard to identifying and studying these interventions using SEER-Medicare data. By proposing 1 approach to categorizing TX lines for mCC patients, we hope to empower the scientific community and to advance the use of SEER-Medicare data for health outcomes research.